Pengaruh Komitmen Kerja, Work Life Balance dan Kepercayaan Diri Terhadap Kinerja Pegawai di Biro Administrasi Pimpinan Sekretariat Daerah Provinsi Sulawesi Tenggara - Pratama, I Gede Aditya Putra; Muthalib, Abd. Azis; Supriadin, Naufal (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyse the influence of organisational commitment, work-life balance and self-confidence on employee performance at the Executive Administration Bureau of the Regional Secretariat of Southeast Sulawesi Province, both simultaneously and individually. The study employs a quantitative approach using a survey method. The sample comprised 31 employees selected using a census technique. Research data were obtained through questionnaires filled out by the respondents. The data were analyzed quantitatively using multivariate regression analysis. The research results show that: 1) Organizational Commitment (X1), work-life balance (X2), and self-confidence (X3) have a positive and significant effect on employee performance (Y) at the Leadership Administration Bureau of the Regional Secretariat of Southeast Sulawesi Province. 2) Organizational Commitment (X1) has a positive and significant effect on employee performance (Y) at the Leadership Administration Bureau of the Regional Secretariat of Southeast Sulawesi Province. 3) Work-life balance (X2) has a positive and significant effect on employee performance (Y) at the Leadership Administration Bureau of the Regional Secretariat of Southeast Sulawesi Province. 4) Self-confidence (X3) has a positive and significant effect on employee performance (Y) at the Leadership Administration Bureau of the Regional Secretariat of Southeast Sulawesi Province.